TANTANGAN DAN STRATEGI BERWIRAUSAHA KULINER LOKAL, STUDI KASUS LENTOG TANJUNG PAK SISNO KUDUS - Wahyudi, Muhamad; Hadiwinarto, Saputra; Mashuri, Dian Imami; Riesha, Riezky Army (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Business dynamics are constantly evolving, and the micro-enterprise sector has significant growth opportunities due to the abundance of entrepreneurs today. Various types of businesses exist within communities, particularly culinary food businesses rooted in local wisdom specific to certain regions. There is substantial potential to enhance micro-economic growth through culinary ventures based on local heritage, such as "Lentog Tanjung" from Kudüs. This traditional dish originates from Kudus City in Central Java and naturally holds a distinct market share within the region. Currently, Lentog Tanjung eateries are proliferating throughout the city of Kudus. The research focuses on Warung Lentog Tanjung Pak Sisno, located in Loram Kulon Village, Jati Subdistrict, Kudus Regency, aiming to analyze and identify the challenges and strategies faced by its owner.This study employs a qualitative descriptive research method, utilizing data collection techniques including observation, interviews, and theoretical references. The findings reveal that Warung Lentog Tanjung Pak Sisno is among the well-known Lentog eateries in Jati Subdistrict, Kudus Regency. Key challenges faced include the need for capital support to expand the business, fluctuating raw material prices impacting profit margins, and competition from similar Lentog businesses as well as other culinary enterprises. Warung Lentog Tanjung Pak Sisno has been successfully operating for over 20 years and continues to thrive amidst evolving business dynamics.